Targeted delivery to macrophages and dendritic cells by chemically modified mannose ligand-conjugated siRNA. Issue 9 (7th May 2022) - Uehara, Keiji; Harumoto, Toshimasa; Makino, Asana; Koda, Yasuo; Iwano, Junko; Suzuki, Yasuhiro; Tanigawa, Mari; Iwai, Hiroto; Asano, Kana; Kurihara, Kana; Hamaguchi, Akinori; Kodaira, Hiroshi; et al.
Abstract: Extrahepatic delivery of small interfering RNAs (siRNAs) may have applications in the development of novel therapeutic approaches. However, reports on such approaches are limited, and the scarcity of reports concerning the systemically targeted delivery of siRNAs with effective gene silencing activity presents a challenge. We herein report for the first time the targeted delivery of CD206-targetable chemically modified mannose–siRNA (CMM–siRNA) conjugates to macrophages and dendritic cells (DCs). CMM–siRNA exhibited a strong binding ability to CD206 and selectively delivered contents to CD206-expressing macrophages and DCs. Furthermore, the conjugates demonstrated strong gene silencing ability with long-lasting effects and protein downregulation in CD206-expressing cells in vivo . These findings could broaden the use of siRNA technology, provide additional therapeutic opportunities, and establish a basis for further innovative approaches for the targeted delivery of siRNAs to not only macrophages and DCs but also other cell types.